Vector control of three-phase AC machines system development in the practice - Quang, Nguyen Phung (Power systems, 2008)
This book covers vector control of three-phase AC machines, in particular induction motors with squirrel-cage rotor, permanent excited synchronous motors and doubly-fed induction machines, from the viewpoint of practical design and development.